Hubungan Pola Asuh Orang Tua dan Budaya dengan Kejadian Cyberbullying pada Remaja : The Relationship between Parenting Patterns and Culture with Cyberbullying Incidents in Adolescents - Nabilah, Alya; Lestari, Nur Eni; Rokhmiati, Eka (MPI Press, 2023)
Introduction: Cyberbullying is an act that will have physical, psychological emotional, psychosocial, and school-related impacts. Objectives: This research was conducted to see the relationship between parenting and culture with the incidence of cyberbullying among adolescents at MTsn 16, East Jakarta 2022. Method: Observational study with a cross-sectional research design. The population in this study were all 9th-grade students at MTsN 16 East Jakarta, totaling 582 students. Meanwhile, the sample to be used was calculated using the Slovin formula, namely 237 students and female students. Modification of the Revised Cyberbullying Inventory (RCBI), while parenting style uses the Parenting Style and Dimension Questionnaire (PSDQ) measurement tool, and culture uses the Middle Schools Environmental Literacy Instrument (MSELI) measurement tool. Result: The results show that there is no relationship between parenting and culture variables and the incidence of cyberbullying in adolescents with a p-value of 0.508 (p-value> 0.05). Conclusion: It is expected that teenage parents will always pay attention to their children when using social media.